Metaethics and psychology: an investigation into the links between autism, OCD, and depression and metaethics - Popat, Riana (2025)
My thesis examines how psychological conditions impact metaethical theories. More precisely, I look at three separate mental health conditions and how they impact three different metaethical theories. My thesis argues that certain mental health perspectives should inform certain metaethical theories. These mental health conditions are Autism, Obsessive compulsive disorder (OCD), and Major Depressive Disorder, and I will look at how these conditions link to three separate metaethical theories, which are Moral Hermeneutic Fictionalism, Weak Motivational Internalism, and the Humean Theory of Motivation. As I will argue in this thesis that mental health conditions should inform metaethical theories, I will use the mental health conditions specified as case studies to support my overall argument. My findings also yield the conclusion that mental health conditions have different impacts on metaethical perspectives, but nonetheless, these conditions do have an impact on metaethics.